Procoagulant Material From Human Urine in Prothrombin Activation - Caldwell, M June; von Kaulla, Kurt N; von Kaulla, Edith; Seegers, Walter H (Thrombosis and Haemostasis, 1963)
The procoagulant or P fraction obtained from human urine was analyzed to determine how it functions in the activation of purified prothrombin. Prothrombin converts to thrombin in the presence of P fraction, Ac-globulin, calcium chloride and either whole platelets or platelet factor 3. The yield of thrombin can be made to depend upon the concentration of P fraction. This conversion of prothrombin to thrombin can be partially or completely inhibited by adding various concentrations of soybean trypsin inhibitor introduced into the activation mixture.When purified prothrombin was activated with platelet factor 3 and calcium chloride, the prothrombin activity, as measured by the two-stage assay, decreased. When it was at the lowest possible level, P fraction was added. Quite quickly prothrombin activity began to reappear, and soon 100% of the original prothrombin activity was accounted for as either prothrombin-R or thrombin.